PENGARUH PENERAPAN MODEL PEMBELAJARAN AKTIF TIPE MIND MAPPING TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN MATEMATIKA KELAS VIII MTsN BATANG KAPAS TAHUN PELAJARAN 2013/2014 - Pianti, Nova Depita; Rismen, Sefna; K, Delsi. (Pendidikan Matematika, 2013)
This research was motivated by the mathematics learning outcomes achieved by students of class VIII MTsN Batang Kapas is still below the minimum completeness criteria (KKM). The purpose of this study was to determine whether the average ability of students mathematics learning outcomes by using a Mind Mapping learning strategy type is better than the average results of students mathematics learning with conventional learning in class VIII MTsN batang Kapas.This research is a kind of experiment . The population in this study were all eighth grade students enrolled MTsN Batang Kapas in the school year 2013/2014 . whereas the sample in this study is as experimental class VIII A and VIII D as the control class . The instrument used is the achievement test . The form of an essay test that is used with a reliability of 0.81. Technique analysis achievement test prepared by t. Analyses data performed with the help of MINITAB software , obtained from the calculation of P - value = 0.009 is less than Î± = 0.05 . Therefore we can conclude the average mathematics achievement of students with learning strategy type using Mind Mapping is better than the average results of students mathematics learning with conventional learning in class VIII MTsN Batang Kapas 2013/2014 .